2020
DOI: 10.1177/2153368720973442
|View full text |Cite
|
Sign up to set email alerts
|

Adult Outcomes of Justice Involved Indigenous Youth

Abstract: Juvenile arrest serves as a critical turning point in the life-course that disrupts the successful transition to adulthood and carries numerous consequences including diminished socioeconomic status. Despite their disproportionately high rates of contact with the criminal justice system (CJS), Indigenous people’s experiences remain largely invisible in extant research. Further, colonization has left them in an extremely marginalized position in terms of social, economic, and political power, which is compounde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 66 publications
2
6
0
Order By: Relevance
“…Another particularly important finding is that youth of Indigenous descent are at increased risk of being opined incompetent among JSOs. Although Indigenous youth are incredibly underrepresented in the juvenile justice literature and further study on this population is needed [48], this finding aligns with a previous study that found Indigenous youth in New Zealand were more likely than youth of other backgrounds to be opined incompetent [49].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Another particularly important finding is that youth of Indigenous descent are at increased risk of being opined incompetent among JSOs. Although Indigenous youth are incredibly underrepresented in the juvenile justice literature and further study on this population is needed [48], this finding aligns with a previous study that found Indigenous youth in New Zealand were more likely than youth of other backgrounds to be opined incompetent [49].…”
Section: Discussionsupporting
confidence: 86%
“…Available evidence suggests that Indigenous youth may experience differential treatment and outcomes as a result of juvenile justice involvement [48], and this may include measurement bias in assessment/evaluation procedures [50]. Previous research among adults referred for adjudicative competence evaluations has found that assessment items related to appreciation of charges and potential outcomes are more subjective and favorably biased toward White respondents, compared with respondents of color [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we are only able to examine arrests using these data, clearance patterns can shed important insight on broader police-community interactions (Cook 1979); recent research on the consequences of arrest among AIAN people has also demonstrated that arrest itself contributes to significant socioeconomic inequalities. Sittner and Estes (2020), for example, found that arrest of Indigenous youth was associated with higher rates of unemployment, lower income, and lower educational attainment, regardless of later criminal justice outcomes. But the decision to arrest a suspect is also hugely consequential in predicting other punishment outcomes (Shermer and Johnson 2010).…”
Section: Discussionmentioning
confidence: 99%